Inhibitory effect of unsaturated fatty acids on saturated fatty acid-induced apoptosis in human pancreatic β-cells: activation of caspases and ER stress induction - Němcová-Fürstová, Vlasta; James, Roger F L; Kovář, Jan (Cellular physiology and biochemistry, 2011)
AIMS: In this study we have tested the effect of unsaturated fatty acids on the proapoptotic effects of saturated fatty acids in the human pancreatic β-cells NES2Y. RESULTS: We found that unsaturated palmitoleic and oleic acid at a concentration of 0.2 mM and higher are able to completely inhibit the proapoptotic effect of their counterpart saturated palmitic and stearic acid at a concentration of 1 mM. Apoptosis induced by stearic acid was associated with significant activation of caspase-6, -7, -9, -2 and -8, but not with significant activation of caspase-3. The activation of caspases was blocked by coincubation with oleic acid. Stearic acid treatment was not associated with a significant change in mitochondrial membrane potential, reactive oxygen species level and with cytochrome c release from mitochondria. Furthermore, stearic acid treatment was not associated with changes in p21(WAF1/CIP1), PIDD, Fas receptor and Fas ligand expression. However, we detected endoplasmic reticulum (ER) stress markers, i. e. a significant upregulation of BiP and CHOP expression as well as XBP1 mRNA splicing. These changes were inhibited by coincubation with oleic acid. CONCLUSION: Presented data indicate that oleic acid inhibits apoptosis induction by stearic acid in NES2Y cells upstream of caspase activation and ER stress induction. It does not involve an interference with the mitochondrial pathway of apoptosis induction, with p53 activation and PIDD expression as well as with Fas receptor and Fas ligand expression.
Keywords: DNA vazebné proteiny; aktivace enzymů; Stress, Physiological; apoptóza; Stearic Acids; cytochromy c; Fatty Acids, Monounsaturated; Caspases; sestřih RNA; transkripční faktory; průtoková cytometrie; Enzyme Activation; Membrane Potential, Mitochondrial; Mitochondria; RNA Splicing; Apoptosis; Up-Regulation; Heat-Shock Proteins; Cell Line, Transformed; beta-buňky; lidé; Oleic Acid; Endoplasmic Reticulum; kyselina olejová; Flow Cytometry; transkripční faktor CHOP; upregulace; Transcription Factors; messenger RNA; fyziologický stres; mitochondrie; RNA, Messenger; Transcription Factor CHOP; Cytochromes c; membránový potenciál mitochondrií; Insulin-Secreting Cells; DNA-Binding Proteins; exprese genu; kyseliny stearové; kyseliny mastné mononenasycené; kaspasy; endoplazmatické retikulum; transformované buněčné linie; proteiny teplotního šoku; Gene Expression; Humans